Alternative Exams in Khartoum University, Case Study from College of Science - Mohammed Abu Eliwa, Hind; Ali Abumalloh, Rabab; Abu-Ulbeh, Waheeb (International Journal of Psychosocial Rehabilitation, 2020)
This study addresses the issue of alternative examinations at Sudanese universities; an issue that has remarkably stricken a phenomenal presence recently. The research aims at studying the factors affect such a phenomenon and the reasons why student choose this type of examinations and what they reap out of it. It also recommends ways of averting that problem. The descriptive-analytical method is used in the study. The research community was the University of Khartoum and the research sample consisted of the Faculty of Science. The faculty was deliberately selected because of the many medical reports presented thereto. A comprehensive survey was conducted on all medical reports issued in one academic year, from the start-up to the end of the supplementary and alternative examinations. A comparison between the numbers of reports between the faculty of science and faculty of economic was conducted. One of the general findings is that there is significant difference between the percentage of reports in the faculties of science of the universities of Khartoum. In both universities, the percentage of reports issued during the final examinations is significantly greater than that during the academic year. Also, reports of female students are greater in number than those of male students; and external reports exceed internal ones.